Veterans' Interpretation of Diabetes Distress in Diabetes Self-Management: Findings From Cognitive Interviews. Issue 5 (October 2021) - Lewinski, Allison A.; Shapiro, Abigail; Bosworth, Hayden B.; Crowley, Matthew J.; McCant, Felicia; Howard, Teresa; Jeffreys, Amy S.; McConnell, Eleanor; Tanabe, Paula; Barcinas, Susan; Coffman, Cynthia J.; King, Heather A.
Purpose: The purpose of this project was to identify additional facets of diabetes distress (DD) in veterans that may be present due to the veteran's military-related experience. Methods: The study team completed cognitive interviews with veterans with type 2 diabetes mellitus (T2DM) to examine how they answered the Diabetes Distress Scale (DD Scale), a tool that assesses DD. The DD Scale was used because of its strong associations with self-management challenges, physician-related distress, and clinical outcomes. Results: The veterans sample (n= 15) was 73% male, mean age of 61 (SD = 8.6), 53% Black, 53% with glycosylated hemoglobin level <9%, and 67% with prescribed insulin. The DD Scale is readily understood by veterans and interpreted. Thematic analysis indicated additional domains affecting DD and T2DM self-management, including access to care, comorbidities, disruptions in routine, fluctuations in emotions and behaviors, interactions with providers, lifelong nature of diabetes, mental health concerns, military as culture, personal characteristics, physical limitations, physical pain, sources of information and support, spirituality, and stigma. Conclusions: This study describes how a veteran's military experience may contribute to DD in the context of T2DM self-management. Findings indicate clinicians and researchers should account for additional domains when developing self-management interventions and discussing self-management behaviors with individuals with T2DM.